Data Analytic in Internal Auditing: A Scoping Review - Dushyirehamwe, Anne Marie; Utami, Helianti; Diana Tien Irafahmi (Journal of Applied Business, Taxation and Economics Research, 2024)
Technology has become a more significant component of internal and external audits, and rapid changes are occurring in auditing procedures to reflect developments in the business world. This study aims to review existing literature on Data Analytics in Internal Auditing. The research utilizes the scoping review method, which follows the protocol established by Arksey and O'Malley (2005). The investigation has 20 years of observation, from 2003 to 2023. Thirty-nine articles were selected from electronic databases: Sage Journals, Springer, Taylor & Francis, Wiley, Emerald Publish, and Science Direct. The mapping research demonstrates the growth of data analytics in internal auditing. Key findings indicate that data analytics offers numerous advantages for internal auditing, including improved risk identification, enhanced fraud detection, increased operational efficiency, and better decision-making support. However, significant challenges persist, including issues related to data quality, skills gaps, organizational resistance, and technological constraints, emphasizing its crucial role in improving internal audit effectiveness and efficiency and indicating which skills internal auditors need to gain knowledge about internal auditing technology. The Review concludes by identifying gaps in the literature and suggesting future research directions to further advance our understanding of data analytics in internal audits and its implications for organizational performance and compliance.